American Volleyball Coaches Association
The AVCA web site is designed to provide you with information, up-to-date results, job openings, available playing dates, educational materials and the latest articles on sports medicine and coaching. Our goal is to provide our members with instant information about volleyball and the AVCA. We welcome your feedback and suggestions for improvement, additions and links. Check out Collegiate Game for information about the current men's season. Polls, results, tournament schedules, ticket information and awards winners are included. The following articles are offered as full-text-version: SPORTS MEDICINE AND PERFORMANCE COMMISSION POSITION STATEMENT ADDRESSING10-AND-UNDER NATIONAL CHAMPIONSHIP Adopted 1/98, USAV Board of Directors NATIONAL CHAMPIONSHIP COMPETITION for 10-YEAR-OLD and UNDER PLAYER Support Research and Reference Document PERFORMANCE ENHANCEMENT SECTION SELECTIONS VOLLEYBALL SKILL ACQUISITION AND VISUAL/PERCEPTUAL SKILLS REFERENCES THE BIOMECHANICS OF BLOCKING by Peter Vint SIDELINES: Sports Science Spotlight, (Volume 7, Issue II, Summer 1996) ASYMMETRICAL LOADING OF LEAD AND LAG LEGS DURING LANDING OF BLOCKING MOVEMENTS by Jill L. McNitt-Gray, Barry A. Munkasy, Witaya Mathiyakom, Nancy Hillman Somera BIBLIOGRAPHY OF BIOMECHANICS RESEARCH -1963-1997 BIBLIOGRAPHY OF JUMPING AND APPLIED MUSCLE FUNCTION PROPHYLACTIC ANKLE BRACING by Jonathan C. Reeser JUMPERS KNEE: Who is at Risk? by William W. Briner THE RELATIONSHIP BETWEEN AND PSYCHOSOCIAL CLIMATE OF TEAMS AND PLAYER MOTIVATION SIDELINES: Sports Science Spotlight (Volume 8, Issue I, Spring 1997) PSYCHOLOGICAL SKILLS: Differences Between Volleyball Players on the National Youth Team and Those Involved in the 14s High-Performance Camp by Sally A. White Volleyball USA (Summer 1996) EATING DISORDERS: Ethnic Differences of Volleyball Players by Deborah J. Rhea BODY IMAGE PERCEPTIONS of FEMALE ADOLESCENT VOLLEYBALL PLAYERS By Deborah Rhea BENEFITS OF POST SEASON STRENGTH TRAINING by Greg Brislin SIDELINES: Sports Science Spotlight (Winter 1996, Volume 7, Number 4) VOLLEYBALL PLAYER'S GUIDE TO SAFE PLYOMETRICS by Greg Brittenham THE ROLE OF STRETCHING AND FLEXIBILITY TRAINING IN THE PREVENTION OF VOLLEYBALL INJURIES by Jonathan C. Reeser